A survey on distribution and toxigenicity of Aspergillus flavus from indoor and outdoor hospital environments - Sepahvand, Asghar; Shams-Ghahfarokhi, Masoomeh; Allameh, Abdolamir; Jahanshiri, Zahra; Jamali, Mojdeh; Razzaghi-Abyaneh, Mehdi (Folia microbiologica, 2011)
In the present study, genetic diversity and mycotoxin profiles of Aspergillus flavus isolated from air (indoors and outdoors), levels (surfaces), and soils of five hospitals in Southwest Iran were examined. From a total of 146 Aspergillus colonies, 63 isolates were finally identified as A. flavus by a combination of colony morphology, microscopic criteria, and mycotoxin profiles. No Aspergillus parasiticus was isolated from examined samples. Chromatographic analyses of A. flavus isolates cultured on yeast extract-sucrose broth by tip culture method showed that approximately 10% and 45% of the isolates were able to produce aflatoxin B(1) (AFB(1)) and cyclopiazonic acid (CPA), respectively. Around 40% of the isolates produced sclerotia on Czapek-Dox agar. The isolates were classified into four chemotypes based on the ability to produce AF and CPA that majority of them (55.5%) belonged to chemotype IV comprising non-mycotoxigenic isolates. Random amplified polymorphic DNA (RAPD) profiles generated by a combination of four selected primers were used to assess genetic relatedness of 16 selected toxigenic and non-toxigenic isolates. The resulting dendrogram demonstrated the formation of two separate clusters for the A. flavus comprised both mycotoxigenic and non-toxigenic isolates in a random distribution. The obtained results in this study showed that RAPD profiling is a promising and efficient tool to determine intra-specific genetic variation among A. flavus populations from hospital environments. A. flavus isolates, either toxigenic or non-toxigenic, should be considered as potential threats for hospitalized patients due to their obvious role in the etiology of nosocomial aspergillosis.
Keywords: nemocnice; Írán; molekulární sekvence - údaje; půdní mikrobiologie; Iran; Equipment and Supplies, Hospital; mykotoxiny; Mycotoxins; Soil Microbiology; Hospitals; Molecular Sequence Data; Phylogeny; fylogeneze; Air Microbiology; vybavení a zásoby nemocnice; mikrobiologie vzduchu; Aspergillus flavus